Analysis of Illegal Temporary Waste Shelters (TPSS) in Alam Barajo Sub-district Jambi City - Femilia Ramadani, Anisa; Mekarisce, Arnild Augina; Aulia Rahmat, Andree (Rifa'Institute, 2025)
Introducction: Alam Barajo Sub-district in Jambi City has been identified as the area with the highest waste generation, estimated at 79,202 tons per day or 28,988 tons annually, with a population of 101,350 as of 2022. Despite this high volume of waste, four illegal Temporary Waste Shelters (TPSS) were identified in the region. Objective: The purpose of this study is to Analyze Illegal Temporary Waste Shelters in Alam Barajo Sub-district, Jambi City. Method: A qualitative research method with a descriptive approach was applied, focusing on data collected between November 2024 and January 2025. The research explored several variables: the distribution and locations of illegal TPSS, contributing factors to their existence, their environmental and public health impacts, and the current management efforts in place. Results and Discussion: Distribution variables have been carried out in every illegal waste shelter, causal variables such as lack of public awareness, limited facilities and implementation of waste management regulations, causing environmental impacts and health risks. Efforts made by the government include improving facilities, educating the public, and enforcing applicable regulations. Conclusion: The findings revealed that the proliferation of illegal TPSS is mainly driven by low public awareness, inadequate official waste facilities, and weak enforcement of waste management regulations. These conditions contribute to environmental degradation and pose health risks, as accumulated waste serves as a breeding ground for disease vectors. Government efforts include infrastructure improvements, public education, and stricter enforcement.